1989
DOI: 10.1177/0148607189013005557
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac Thrombus Complicating Prolonged Parenteral Nutrition in an Adult

Abstract: Calcified intracardiac thrombi were identified in a 23-year-old man who had received home parenteral nutrition (HPN) for 4 years on account of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Actually, a reduction in heparin concentration from 1000 to 100 IE/mL in the 5 mL catheter lock in 1991 was associated with a decrease in the CRVT incidence. The position of the CVC tip has always been ensured by chest x‐ray in our cohort, as placement of the CVC tip distant from the atriocaval junction has shown an increased risk of CRVT . In the literature, it has been suggested that the occurrence of CRVTs predisposes for CRBSIs or even vice versa .…”
Section: Discussionmentioning
confidence: 86%
“…Actually, a reduction in heparin concentration from 1000 to 100 IE/mL in the 5 mL catheter lock in 1991 was associated with a decrease in the CRVT incidence. The position of the CVC tip has always been ensured by chest x‐ray in our cohort, as placement of the CVC tip distant from the atriocaval junction has shown an increased risk of CRVT . In the literature, it has been suggested that the occurrence of CRVTs predisposes for CRBSIs or even vice versa .…”
Section: Discussionmentioning
confidence: 86%